Short-term changes in plasma and milk fatty acid profiles in cows fed chopped elephant grass-based diets containing two types of sunflower oil associated with two methods of concentrate feeding - Lopes, Fernando César Ferraz; Ribeiro, Carlos Gustavo Santos; Rodriguez, Norberto Mario; Gama, Marco Antônio Sundfeld da; Morenz, Mirton José Frota (Semina: Ciências Agrárias, 2021)
The study was carried out in a randomized block design, in a 2 x 2 factorial arrangement, with the aim to evaluating during 21 days the short-term changes in plasma and milk fatty acid (FA) profile in Holstein x Gyr cows (444±84 kg; 75±31 days in milk; 15.4±4.8 kg day-1 of milk) fed 600 g kg-1 DM chopped elephant grass-based diets supplemented with 45 g kg-1 DM sunflower oil (SO). Two types of SO were evaluated: high oleic/low linoleic acid (HO) and medium oleic/medium linoleic acid (MO). The concentrates containing the SO were supplied separately from the forage twice a day (TAD) or as part of a total mixed ration (TMR). Temporal changes were analyzed by mixed models (P<0.05) using six, four and seven repeated measures over time for FA intake, plasma and milk FA composition, respectively. There was higher oleic acid intake in HO SO-fed cows while higher linoleic and ?-linolenic acids intake was observed in MO SO-fed cows. The TAD-fed cows had higher plasma vaccenic acid content than TMR-fed cows, while MO SO-fed cows had higher plasma vaccenic and rumenic acid contents than HO-fed cows. As a function of the day, there were linear increases for oleic and linoleic acids intake, plasma contents of oleic, vaccenic and linoleic acids, and milk fat content of linoleic acid, while quadratic effects were adjusted for milk fat contents of palmitic, oleic, vaccenic and rumenic acids. In comparison with TMR-fed cows, the milk fat of TAD-fed cows produced between days 13-17 showed a FA profile more nutritionally desirable for human health with lower contents of hypercholesterolemics FAs and higher contents of oleic, rumenic and vaccenic acids. Between days 15-16, the vaccenic and rumenic acids contents in milk fat of MO SO-fed cows were 81% higher than that obtained from HO SO-fed cows, which on the 14th day, had 14% higher oleic acid content in milk fat. Lower milk fat level of hypercholesterolemic FAs was produced between days 13-14 by cows fed with both types of SO.